2018
DOI: 10.1525/mp.2018.36.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Recognition of Timbre Sequences

Abstract: The goal of the current study was to explore outstanding questions in the field of timbre perception and cognition—specifically, whether memory for timbre is better in trained musicians or in nonmusicians, whether short-term timbre recognition is invariant to pitch differences, and whether timbre dissimilarity influences timbre recognition performance. Four experiments examined short-term recognition of musical timbre using a serial recognition task in which listeners indicated whether the orders of the timbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…For example, semantic interference was found only for the natural instrument signals in Experiment 2a, and musicians outperformed nonmusicians on these stimuli. This may seem to confirm research supporting the positive effects of musical training on the encoding of timbral properties (Chartrand & Belin, 2006; Siedenburg & McAdams, 2018). Why did synthesizers in Experiment 2a fail to elicit the same magnitude of effect as natural instruments?…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…For example, semantic interference was found only for the natural instrument signals in Experiment 2a, and musicians outperformed nonmusicians on these stimuli. This may seem to confirm research supporting the positive effects of musical training on the encoding of timbral properties (Chartrand & Belin, 2006; Siedenburg & McAdams, 2018). Why did synthesizers in Experiment 2a fail to elicit the same magnitude of effect as natural instruments?…”
Section: Discussionsupporting
confidence: 76%
“…Does extensive exposure to certain instrumental timbres and timbre-descriptive lexicons strengthen automaticity of cross-modal associations? Musical training has been shown to play a role in some perceptual evaluations of timbre (Chartrand & Belin, 2006; McAdams, Douglas, & Vempala, 2017; Siedenburg & McAdams, 2018; but see Filipic, Tillmann, & Bigand, 2010): we may expect, then, that trained musicians will possess a more finely tuned timbre–semantic repertoire than nonmusicians. On the other hand, if cross-modal correspondence reflects some degree of synesthetic congruency, then musical background would plausibly play an indeterminate role.…”
Section: Study Aimmentioning
confidence: 99%
“…As sequence length increased, discrimination accuracy decreased significantly for the loudness sequences while discrimination accuracy decreased only marginally for pitch and timbre. Furthermore, it has been found that musicians perform significantly better at short-term recognition of variable-pitch sequences than non-musicians, though there was no significant difference in performance between musicians and non-musicians in discriminating constant-pitch sequences (Siedenburg & McAdams, 2018). A recent study by Graves and colleagues (2019) on congenital amusia, a neurodevelopmental disorder in which individuals exhibit a deficit in musical perception, examined individuals with amusia performing a short-term memory task in which they had to extract pitch, brightness, and loudness contours using novel melodies.…”
Section: Introductionmentioning
confidence: 99%